1989
DOI: 10.3109/17453678909150116
|View full text |Cite
|
Sign up to set email alerts
|

Function after tibial osteotomy for medial gonarthrosis below aged 50 years

Abstract: Twenty-seven patients (28 knees), with a median age of 42 (27-50) years treated with a high tibial osteotomy for early medial gonarthrosis (Ahlbäck's Stage I) were examined after 11 (7-18) years. Twenty-four were men; 18 knees had had previous meniscus and ligament lesions. At follow-up, 22 knees were satisfactory and 9 patients managed high-activity sports or heavy work. In 25/28 knees, the arthrotic process had not progressed radiographically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 20 publications
3
53
1
2
Order By: Relevance
“…Two studies reported a high survival rate in patients younger than 50 years, but there is no comparison with an older group and no regression analysis [15,18]. The results of our study indicate a significantly higher failure rate in patients over 65 years.…”
Section: Discussionsupporting
confidence: 63%
“…Two studies reported a high survival rate in patients younger than 50 years, but there is no comparison with an older group and no regression analysis [15,18]. The results of our study indicate a significantly higher failure rate in patients over 65 years.…”
Section: Discussionsupporting
confidence: 63%
“…A Swedish study reported a 33% return rate for high-activity sport and heavy labor after high tibial osteotomy. 20 Forty-seven percent of athletes were able to return to intensive-level sports after combined ACL reconstruction and high tibial osteotomy. 3 Our data did not show any significant effect of isolated or combined adjuvant procedures on the return to sport after autologous chondrocyte transplantation in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with varus deformity in their knees are advised to be undergoing corrective surgery as soon as possible (1, 12, 13). There are two techniques of open and close wedge osteotomies.…”
Section: Discussionmentioning
confidence: 99%